A new species of Bembecia from China, with a catalogue of Chinese species of the genus (Lepidoptera: Sesiidae) - Gorbunov, Oleg G.; Krupitsky, Anatoly V.; Marusov, Anatoly A. (Zootaxa, 2017)
A new species, Bembecia altyntaghica sp. nov. from the Altyn-Tagh Mts., Gansu, West China, is described and illustrated. The data on its biotope and host plant are presented and illustrated as well. An annotated catalogue of the Chinese members of the genus Bembecia is added to this paper. The catalogue contains the following information: the references to the original descriptions, information on name-bearing types, complete bibliographies of the presented taxa, data on host plants and distribution. Here below the Oriental species Bembecia fortis Diakonoff, 1967 is transferred to the genus Oligophlebia Hampson, 1893 comb. nov. (Sesiidae: Paraglosseciini).